Cubic phase rare earth doped hafnium oxide thin film and preparation method and application thereof
Through dual-target magnetron sputtering technology of hafnium oxide ceramic target and rare earth target, a cubic phase rare earth doped hafnium oxide film is formed, which solves the problem of heat damage to hafnium oxide film under high-energy laser, and improves the stability and performance of the film , suitable for the manufacturing of optical components of high-energy laser systems.
Patent Information
- Application Number
- CN202411596458.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing hafnium oxide optical film materials are prone to thermal damage, film layer falls off and fail under high-energy laser radiation, and the preparation process is complex and costly, making it difficult to ensure stability and purity.
Dual-target magnetron sputtering is used to use hafnium oxide ceramic target and rare earth target to stabilize solid solution doping through rare earth elements to form a cubic rare earth-doped hafnium oxide film, which improves thermal conductivity and high-temperature phase stability, simplifies the process and reduces costs.
It significantly improves the laser damage threshold and anti-laser high-temperature ablation performance of the film, enhances adhesion and stability, and is suitable for optical component manufacturing of high-energy laser systems.
Smart Images

Figure CN119144929A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of laser optics and relates to a cubic rare earth doped hafnium oxide film and a preparation method and application thereof. Background Art
[0002] With the increasingly widespread application of ultra-strong laser systems in the fields of weapon guidance, space electronic countermeasures and laser-induced nuclear fusion, the demand for the laser damage resistance of the optical components of the system is also increasing. Taking the laser weapon system as an example, the optical components in its laser optical system generally use optical ceramic glass. However, the material's own transmittance is generally lower than 85% at the laser wavelength, and the laser energy absorption rate exceeds 10%. This absorption phenomenon will cause it to easily absorb laser energy under high-energy laser irradiation and produce cracks or even breakage, making it impossible to achieve the continuous and stable application of high-energy laser systems. Plating a single layer or multiple layers of optical film on the surface of its optical element changes the incident laser light path, and realizes the optical element's anti-transmission for laser, thereby improving the overall laser damage resistance of the optical system. In addition, taking the laser protection of laser infrared detectors as an example, plating a single layer or multiple layers of optical film on the surface of its optical element changes the incident laser light path, realizes total reflection of the laser, and prevents its infrared sensor from being damaged by laser blinding, thereby increasing the overall laser damage resistance of the laser detector. Therefore, the laser damage resistance of the optical film itself determines the laser damage resistance of the entire optical element.
[0003] The essence of laser damage to optical films under laser irradiation is the absorption of laser energy by the film material itself, resulting in thermal damage. Therefore, screening materials with low laser intrinsic absorption and high refractive index for the preparation of laser optical films is one of the effective ways to improve their resistance to laser damage. At present, metal materials and dielectric film materials are both commonly used high laser damage threshold film materials. Compared with metal materials, dielectric film materials have higher transmittance, lower laser intrinsic absorption and high refractive index in the ultraviolet to infrared spectrum range, and are widely used as coating materials for laser optical components.
[0004] At present, dielectric thin film materials are mainly single-component hafnium oxide and zirconium oxide. However, pure hafnium oxide optical thin film materials have problems such as low thermal conductivity and low thermal expansion coefficient. Therefore, due to the energy accumulation effect, the temperature of the film system rises sharply under the laser, causing high-temperature phase transition and film shedding, which eventually leads to the failure of the optical film.
[0005] At the same time, in the preparation of hafnium oxide thin films, methods such as electron beam physical vapor deposition, pulsed laser deposition and sol-gel method are usually used. However, these methods have problems such as high preparation cost, complex process, difficult to ensure stability, difficult to control complex film systems, and difficulty in industrialization. On the other hand, such as the sol-gel method, although it has the advantage of low cost due to the combination of thin film coating process, it has problems such as low material purity, many impurities, difficulty in ensuring the uniformity of large-scale nano-scale film thickness, high toxicity and environmental pollution. More importantly, the solution method is not suitable for the preparation of optical components with complex film structures.
[0006] Therefore, it is necessary to develop new material systems and preparation processes, and through this process, improve the thermal conductivity of hafnium oxide films and improve their high-temperature thermal stability, so as to further promote the development and application of high-power laser technology and enhance economic benefits. Summary of the invention
[0007] In view of the problems existing in the prior art, the purpose of the present invention is to provide a cubic phase rare earth doped hafnium oxide film and its preparation method and use. The preparation method uses a specific hafnium oxide ceramic target and a rare earth target to perform dual-target magnetron sputtering to obtain a cubic phase rare earth doped hafnium oxide film. Compared with a single component hafnium oxide film, the rare earth doped hafnium oxide film obtained by the specific preparation method has a higher laser damage threshold and better intrinsic transmittance, and has a higher thermal conductivity and smaller lattice thermal expansion, so that the film has better high-temperature phase stability and effectively avoids film failure caused by laser thermal damage.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing a cubic rare earth doped hafnium oxide film, the preparation method comprising performing dual-target magnetron sputtering using a hafnium oxide ceramic target and a rare earth target, and allowing the rare earth element to occupy the lattice site of hafnium during the deposition process to achieve stable solid solution doping, so as to obtain a cubic rare earth doped hafnium oxide film.
[0010] The present invention adopts hafnium oxide ceramic target instead of hafnium metal target, which is more conducive to achieving nanoscale uniform mixing between hafnium oxide and rare earth elements, and can not only ensure that hafnium oxide has a stable and ideal composition ratio, but also can adjust the doping amount by adjusting the sputtering parameters of the rare earth target during the co-sputtering process, greatly simplifying the process and improving the process stability, thereby obtaining a stable cubic phase rare earth doped hafnium oxide film. The pinning effect of rare earth elements on the lattice is used to effectively improve the stability of the system and the thermal expansion coefficient of the film, thereby effectively improving the film shedding defects caused by the phase change expansion of the material lattice at high temperature; rare earth elements doped hafnium oxide, the film changes from an amorphous phase to a cubic phase at low temperature, and the structure is more symmetrical and regular, so it has a higher thermal conductivity. In summary, doping with rare earths can make the resulting cubic phase rare earth doped hafnium oxide film have a high laser damage threshold, better resistance to laser high temperature ablation and better adhesion, which is more conducive to manufacturing more stable laser optical components and providing support for high-energy laser systems. The preparation method realizes doping-preparation integration, reduces the process flow, reduces the manufacturing cost, and ensures the acquisition of a cubic rare earth-doped hafnium oxide film with high adhesion, high density and high performance and resistance to laser damage.
[0011] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0012] As a preferred technical solution of the present invention, the rare earth element in the rare earth target includes at least one of Y, Er, Yb, Eu or Sc.
[0013] Preferably, in the cubic rare earth-doped hafnium oxide thin film, the molar doping amount of the rare earth element is 5% to 20% of the molar amount of hafnium oxide, for example, 5%, 8%, 10%, 12%, 14%, 16%, 18% or 20%.
[0014] As a preferred technical solution of the present invention, the hafnium oxide ceramic target is matched with a radio frequency power supply for magnetron sputtering.
[0015] Preferably, the rare earth target comprises a metal target or a compound target of a rare earth element, preferably a metal target.
[0016] Preferably, the compound target includes an oxide target.
[0017] Preferably, when the rare earth target is a metal target, a DC power supply is matched to perform magnetron sputtering; when the rare earth target is a compound target, a radio frequency power supply is matched to perform magnetron sputtering.
[0018] Preferably, the purity of the hafnium oxide ceramic target and the rare earth target is ≥99.99%.
[0019] As a preferred technical solution of the present invention, the dual-target magnetron sputtering includes first performing pre-sputtering for 1 to 5 minutes, such as 1 minute, 2 minutes, 3 minutes, 4 minutes or 5 minutes, and then performing co-sputtering.
[0020] Preferably, in the dual-target magnetron sputtering, the background vacuum of the chamber is 3×10 -5 ~9×10 -4 Pa, for example 3×10 - 5 Pa, 5×10 -5 Pa, 8×10 -5 Pa, 1×10 -4 Pa, 3×10 -4 Pa, 5×10 -4 Pa, 7×10 -4 Pa or 9×10 -4 Pa, etc.; argon is used as the working gas, and the flow rate of the working gas is 20~60sccm, for example, 20sccm, 25sccm, 30sccm, 35sccm, 40sccm, 45sccm, 50sccm, 55sccm or 60sccm, etc.; the working vacuum degree is 0.1~1Pa, for example, 0.1Pa, 0.3Pa, 0.5Pa, 0.8Pa or 1Pa, etc.
[0021] Preferably, in the dual-target magnetron sputtering, the sputtering power of the hafnium oxide ceramic target is 200-250W, such as 200W, 210W, 220W, 230W, 240W or 250W, etc., and the sputtering power of the rare earth target is 10-200W, such as 10W, 12W, 15W, 18W, 20W, 23W, 25W, 28W, 30W, 50W, 80W, 100W, 120W, 140W, 160W, 180W or 200W, etc. Further preferably, when the rare earth target is subjected to DC sputtering, the DC sputtering power is 10-30W; when the rare earth target is subjected to RF sputtering, the RF sputtering power is 30-200W.
[0022] Preferably, in the dual-target magnetron sputtering, the ratio of the molar doping amount of the rare earth element to the molar amount of hafnium oxide is controlled by regulating the sputtering power of the rare earth target.
[0023] Preferably, after the dual-target magnetron sputtering is completed, a composite film is obtained, and the composite film is annealed to obtain the cubic rare earth-doped hafnium oxide film.
[0024] Preferably, the annealing temperature is 100-500°C, for example, 100°C, 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C or 500°C.
[0025] In the present invention, the film thickness of the cubic rare earth doped hafnium oxide film can be controlled by sputtering power, working pressure, substrate temperature, and sputtering time. The present invention mainly controls the sputtering time to obtain the target thickness without changing other process parameters. When the cubic rare earth doped hafnium oxide film is used as an optical film, the optical thickness needs to be controlled to an integer multiple of one quarter of the target wavelength to achieve a specific optical function.
[0026] Furthermore, in the present invention, in order to achieve the product of the dual targets at the target rate, the hafnium oxide ceramic target will adopt a higher RF power, and in order to achieve effective cooling of the target, the permanent magnet can also be put into the cooling water circulation in the design of the RF target to increase the heat dissipation area of the target, thereby solving the problem of heat resistance of the ceramic target.
[0027] In a second aspect, the present invention can provide a cubic rare earth doped hafnium oxide thin film obtained according to the preparation method described in the first aspect.
[0028] In a third aspect, the present invention provides a use of the cubic rare earth doped hafnium oxide film described in the second aspect, wherein the use includes use as a laser optical film with a high laser damage threshold.
[0029] As a preferred technical solution of the present invention, the use includes a laser anti-reflection optical element.
[0030] Preferably, the laser anti-reflection optical element comprises an optical substrate and an intermediate layer and a protective layer sequentially arranged thereon, and the intermediate layer comprises the laser optical film with a high laser damage threshold.
[0031] Preferably, the optical thickness of the intermediate layer and the optical thickness of the protective layer are respectively one quarter of the laser wavelength.
[0032] Preferably, the protective layer comprises a SiO2 thin film layer.
[0033] As a preferred technical solution of the present invention, the use includes laser reflection protection optical elements.
[0034] Preferably, the laser reflection protection optical element comprises G|(HL) 10 L|Air structure, wherein G is an optical substrate, H is a high reflectivity film layer, L is a low reflectivity film layer, and the high reflectivity film layer includes the laser optical film with a high laser damage threshold.
[0035] In the present invention, Air means that the last layer L has a surface facing the outside, and the last layer L serves as a protective layer.
[0036] Preferably, the optical thickness of the high reflectivity film layer and the optical thickness of the low reflectivity film layer are respectively one quarter of the laser wavelength.
[0037] It should be noted that the optical thickness of the intermediate layer, the optical thickness of the protective layer, the optical thickness of the high reflectivity film layer and the optical thickness of the low reflectivity film layer of the present invention need to be reasonably adjusted according to the laser wavelength of the target laser to achieve a specific optical function. Generally, the optical thickness of the optical film is preferably one quarter of the laser wavelength of the target laser. The cubic rare earth doped hafnium oxide film, the laser anti-reflection optical element containing the same and the laser reflection protection optical element containing the same of the present invention are preferably designed for lasers with a wavelength of 1064nm, but are not limited to lasers with a wavelength of 1064nm.
[0038] Preferably, the low reflectivity film layer comprises a SiO2 thin film layer.
[0039] The invention is based on the preparation method and the obtained cubic rare earth doped hafnium oxide film with high laser damage threshold, which can be used as a laser optical film to realize the structural and functional integrated design and manufacturing of laser optical elements. The obtained laser anti-reflection optical element has excellent anti-laser damage performance, and the damage threshold of 1064nm high-power laser can reach up to 9.39J / cm 2 , and has excellent optical transmittance, the transmittance of a single band can reach up to 95.9% (compared to the intrinsic transmittance of the quartz substrate 93.6%); the laser reflection protection optical element obtained above has excellent anti-laser damage performance and reflectivity, and the laser damage threshold of 1064nm pulse laser can reach 6.68J / cm 2 Above, the reflectivity can reach up to 99.3%.
[0040] As a preferred technical solution of the present invention, the optical substrate includes at least one of quartz glass, BK7 glass, sapphire glass or organic flexible glass.
[0041] Preferably, the optical substrate is cleaned and dried in advance.
[0042] Preferably, the cleaning method comprises ultrasound, and the drying method comprises nitrogen purging.
[0043] As a preferred technical solution of the present invention, the method for preparing the SiO2 thin film layer comprises: using a silicon oxide target with a purity of ≥99.99% for magnetron sputtering, controlling the background vacuum of the chamber to 3×10 -5 ~9×10 -4 Pa, for example 3×10 - 5 Pa, 5×10 -5 Pa, 8×10-5 Pa, 1×10 -4 Pa, 3×10 -4 Pa, 5×10 -4 Pa, 7×10 -4 Pa or 9×10 -4 Pa, etc.; argon is used as the working gas, and the flow rate of the working gas is 20-60sccm, such as 20sccm, 25sccm, 30sccm, 35sccm, 40sccm, 45sccm, 50sccm, 55sccm or 60sccm, etc.; the working vacuum degree is 0.1-1Pa, such as 0.1Pa, 0.3Pa, 0.5Pa, 0.8Pa or 1Pa, etc. Matching RF power supply, sputtering power is 100-250W, such as 100W, 130W, 150W, 180W, 200W, 220W or 250W, etc.; pre-sputtering is performed for 1-5min, such as 1min, 2min, 3min, 4min or 5min, etc., and then formal sputtering is performed.
[0044] Due to space limitations and to avoid redundancy, the present invention does not list all point values within the above numerical range one by one, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0045] Compared with the prior art solutions, the present invention has at least the following beneficial effects:
[0046] The invention adopts a specific hafnium oxide ceramic target and a rare earth target to perform dual-target magnetron sputtering, which is conducive to achieving nanoscale uniform mixing between the hafnium oxide and the rare earth element, and can ensure that the hafnium oxide has a stable and ideal composition ratio, and can adjust the doping amount by only adjusting the sputtering parameters of the rare earth target during the co-sputtering process, greatly simplifying the process and improving the process stability, thereby obtaining a stable cubic phase rare earth doped hafnium oxide film. The preparation method realizes doping-preparation integration, reduces the process flow, reduces the manufacturing cost, and ensures the acquisition of a high-adhesion, high-density and high-performance cubic phase rare earth doped hafnium oxide film that is resistant to laser damage.
[0047] The present invention utilizes the pinning effect of rare earth elements on the lattice to effectively improve the stability of the system, improve the film shedding defects caused by high-temperature phase change, and thereby make the obtained cubic rare earth-doped hafnium oxide film have a high laser damage threshold, which is conducive to the manufacture of more stable laser optical components and provides support for high-energy laser systems.
[0048] The laser anti-reflection optical element and laser reflection protection optical element made of cubic rare earth doped hafnium oxide film with high laser damage threshold in the present invention both have excellent anti-laser damage performance and reflectivity, realizing the structural and functional integrated design and manufacturing of laser optical elements. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 is a test graph of the intrinsic transmittance of the thin film obtained in Example 1 and the uncoated optical substrate;
[0050] Figure 2 1 is a refractive index test graph of the film obtained in Example 1 and the film obtained in Comparative Example 1;
[0051] Figure 3 is a schematic structural diagram of the laser anti-reflection optical element in Application Example 1;
[0052] Figure 4 is a cross-sectional SEM image of the laser anti-reflection optical element containing the thin film obtained in Example 1 in Application Example 1;
[0053] Figure 5 is a transmittance test diagram of a laser anti-reflection optical element containing the thin film obtained in Example 1 and an uncoated optical substrate in Application Example 1;
[0054] Figure 6 This is a laser damage threshold test diagram of the laser anti-reflection optical element containing the thin film obtained in Example 1 in Application Example 1;
[0055] Figure 7 is a schematic structural diagram of the laser reflection protection optical element in Application Example 2;
[0056] Figure 8 is a cross-sectional SEM image of a laser reflection protection optical element containing the thin film obtained in Example 1 in Application Example 2;
[0057] Fig. 9 is a transmittance test diagram of a laser anti-reflection optical element containing the thin film obtained in Example 1 and an uncoated optical substrate in Application Example 2;
[0058] Fig.10 This is a laser damage threshold test diagram of the laser reflection protection optical element containing the film obtained in Example 1 in Application Example 2;
[0059] Fig.11 A schematic diagram of a magnetron sputtering device capable of implementing the method for preparing the cubic rare earth-doped hafnium oxide thin film of the present invention;
[0060] Fig.12 1 is an XRD crystal phase structure test diagram of the cubic rare earth-doped hafnium oxide thin film obtained in Example 1 and the thin film obtained in Comparative Example 1;
[0061] Figure 3 and Figure 7 Middle: 1-optical substrate, 2-intermediate layer, 3-protective layer, 4-high reflectivity film layer, 5-low reflectivity film layer;
[0062] Fig.11 Middle: 60 - ion source, 70 - sample stage, 71 - in-situ heating stage, 80 - hafnium oxide ceramic target, 81 - rare earth target. DETAILED DESCRIPTION
[0063] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0064] It should be clear to those skilled in the art that the embodiments are only intended to help understand the present invention and should not be considered as specific limitations of the present invention.
[0065] The magnetron sputtering process of the following embodiments, comparative examples and application examples is as follows Fig.11 The magnetron sputtering device shown in the figure has an ion source 60 and a dual target position, which respectively places a hafnium oxide ceramic target 80 (it can also be other hafnium source targets) and a rare earth target 81 to achieve magnetron co-sputtering. The coating substrate (such as an optical substrate) is placed on a sample stage 70, and the sample stage 70 controls the working deposition temperature and annealing temperature through an in-situ heating stage 71.
[0066] Example 1
[0067] This embodiment provides a method for preparing a cubic rare earth-doped hafnium oxide thin film, the preparation method comprising:
[0068] A hafnium oxide ceramic target (3 inches) and a rare earth target (3 inches) with a purity of 99.99% were used for dual-target magnetron sputtering on the substrate. The rare earth target was a yttrium metal target. The hafnium oxide ceramic target was matched with a radio frequency power supply, and the rare earth target was matched with a direct current power supply. The background vacuum of the chamber was controlled to be 8×10 -4 Pa, argon is used as the working gas, the flow rate of the working gas is 30sccm, and the working vacuum is 0.2Pa; the sputtering power of the hafnium oxide ceramic target is 250W, and the sputtering power of the rare earth target is 15W; pre-sputtering is performed for 5 minutes, and then co-sputtering is performed; the molar doping amount of the rare earth element is controlled to be 5% of the molar amount of hafnium oxide to obtain a composite film; the composite film is annealed at 200°C to obtain a cubic rare earth doped hafnium oxide film (cubic yttrium doped hafnium oxide film YHfO x ).
[0069] Example 2
[0070] This embodiment provides a method for preparing a cubic rare earth-doped hafnium oxide film, wherein the rare earth target is matched with a DC power supply, the sputtering power of the rare earth target is 20 W, and the molar doping amount of the rare earth element to the molar amount of hafnium oxide is adjusted from 5% to 10%. Except for the above, other conditions are exactly the same as those in Example 1.
[0071] Example 3
[0072] This embodiment provides a method for preparing a cubic rare earth-doped hafnium oxide film, wherein the rare earth target is matched with a DC power supply, and the sputtering power of the rare earth target is 25 W, so that the molar doping amount of the rare earth element to the molar amount of hafnium oxide is adjusted from 5% to 15%. Except for the above, other conditions are exactly the same as those in Example 1.
[0073] Example 4
[0074] This embodiment provides a method for preparing a cubic rare earth-doped hafnium oxide film, wherein the rare earth target is matched with a DC power supply, and the sputtering power of the rare earth target is 30 W, so that the molar doping amount of the rare earth element to the molar amount of hafnium oxide is adjusted from 5% to 20%. Except for the above, other conditions are exactly the same as those in Example 1.
[0075] Comparative Example 1
[0076] This comparative example provides a method for preparing a hafnium oxide thin film. The preparation method does not use a rare earth target, but only uses a hafnium oxide ceramic target for magnetron sputtering. Except for the above, other conditions are exactly the same as those in Example 1.
[0077] Characterization and Testing I:
[0078] The films obtained in Examples 1-4 and Comparative Example 1 and the uncoated optical substrate were tested for intrinsic transmittance and refractive index, and a laser damage threshold test was performed: the optical transmittance was measured using Shimadzu's SolidSpec-3700i; the laser damage threshold was measured in accordance with the 1-ON-1 method defined in ISO 21254, using a Nd:YAG laser to emit 1064nm, 10ns laser, with a laser repetition rate of 1Hz and a beam spot diameter of 0.8mm.
[0079] Figure 1 This is a test chart of the intrinsic transmittance of the thin film obtained in Example 1 and the uncoated optical substrate. It can be seen from the figure that the intrinsic transmittance of the uncoated optical substrate at 1064nm is 93.6%, and the intrinsic transmittance of the cubic rare earth-doped hafnium oxide thin film at 1064nm is 80.4%.
[0080] Figure 2 3 is a refractive index test diagram of the film obtained in Example 1 and the film obtained in Comparative Example 1. It can be seen from the figure that the refractive index of the pure hafnium oxide film obtained in Comparative Example 1 is 2.07, and the refractive index of the film obtained in Example 1 is 2.1.
[0081] Fig.12 3 is an XRD crystal phase test diagram of the thin films obtained in Example 1 and Comparative Example 1. It can be seen from the figure that the pure hafnium oxide thin film is a monoclinic phase, and the yttrium-doped hafnium oxide thin film exhibits a cubic phase.
[0082] Other results are recorded in Table 1.
[0083] Table 1
[0084] film 1064 nm transmittance (%) <![CDATA[Laser damage threshold (J / cm 2 )]]> Example 1 80.4 7.76 Example 2 78.4 7.25 Example 3 81.6 3.95 Example 4 77.5 2.25 Comparative Example 1 73.7 7.10 Uncoated Optical Substrates 93.6 Not tested
[0085] It can be seen from Table 1 that:
[0086] Although the addition of Y metal can stabilize the HfO2 cubic phase system, the strong absorption and high refractive properties of the metal itself will lead to a decrease in the transmittance of the film and an increase in the refractive index. This will lead to an increase in the film's absorption of laser energy, resulting in the film's laser damage threshold not necessarily increasing steadily with the increase in doping level.
[0087] Application Example 1
[0088] This application example provides a laser anti-reflection optical element, such as Figure 3 As shown, the laser anti-reflection optical element comprises an optical substrate 1 and an intermediate layer 2 and a protective layer 3 sequentially arranged thereon, wherein the intermediate layer 2 is the thin film obtained in Example 1; the protective layer 3 is a SiO2 thin film layer; the optical thickness of the intermediate layer 2 and the protective layer 3 is a quarter wavelength;
[0089] The manufacturing method of the laser anti-reflection optical element comprises:
[0090] (1) preparing a quartz glass plate as an optical substrate 1, immersing the optical substrate 1 in an organic solvent for ultrasonic cleaning for 20 min, then rinsing it with ultrapure water, and finally drying it with nitrogen;
[0091] (2) Using the preparation method provided in Example 1, a thin film with an optical thickness of one quarter of a wavelength is prepared on the optical substrate 1 as the intermediate layer 2;
[0092] (3) Using a silicon oxide target with a purity of ≥99.99%, magnetron sputtering was performed on the obtained intermediate layer 2, and the background vacuum of the chamber was controlled to be 8×10 -4 Pa, argon is used as the working gas, the flow rate of the working gas is 40sccm, the working vacuum is 0.5Pa, the RF power supply is matched, the sputtering power is 150W, a 5-minute pre-sputtering is performed first, and then a formal sputtering is performed to obtain a SiO2 thin film layer with an optical thickness of one quarter of the wavelength as the protective layer 3.
[0093] Characterization and testing II:
[0094] Figure 4This is a cross-sectional SEM image of the laser anti-reflection optical element containing the thin film obtained in Example 1 in Application Example 1. The film layers are divided by white short lines and the number of film layers is displayed in red numbers. It can be seen from the figure that the film layer has a two-layer structure, in which number 1 is a cubic rare earth-doped hafnium oxide layer and number 2 is a silicon dioxide layer.
[0095] The transmittance and laser damage threshold tests were performed on the laser anti-reflection optical element made of the thin film obtained in Example 1 and the uncoated optical substrate (as application comparison example 1): the optical transmittance was measured using Shimadzu's SolidSpec-3700i; the laser damage threshold was measured in accordance with the 1-ON-1 method defined in ISO 21254, using a Nd:YAG laser to emit 1064nm, 10ns laser, with a laser repetition rate of 1Hz and a beam spot diameter of 0.8mm.
[0096] Figure 5 This is a transmittance test chart of the laser anti-reflection optical element containing the thin film obtained in Example 1 and the uncoated optical substrate (or uncoated optical element) in Application Example 1. It can be seen from the chart that the transmittance at a wavelength of 1064nm reaches 95.9%.
[0097] Figure 6 This is a test diagram of the laser damage threshold of the laser anti-reflection optical element containing the film obtained in Example 1 in Application Example 1. It can be seen from the figure that the laser damage threshold of the optical anti-reflection element is 9.39 J / cm 2 .
[0098] It can be seen that the double-layer antireflection film system composed of thin films obtained by depositing an appropriate rare earth doping amount increases the transmittance of optical devices, thereby reducing the overall absorption of laser energy to achieve the purpose of a high laser damage threshold.
[0099] Application Example 2
[0100] This application example provides a laser reflection protection optical element, such as Figure 7 As shown, the laser reflection protection optical element includes G|(HL) 10 L|Air structure, wherein G is an optical substrate 1, H is a high reflectivity film layer 4, L is a low reflectivity film layer 5, and the high reflectivity film layer 5 is the film obtained in Example 1; the low reflectivity film layer 4 is a SiO2 thin film layer, and the optical thickness of the high reflectivity film layer 5 and the low reflectivity film layer 4 is a quarter wavelength;
[0101] The manufacturing method of the laser reflection protection optical element comprises:
[0102] (1) Prepare a quartz glass plate as an optical substrate 1, immerse the optical substrate 1 in an organic solvent for ultrasonic cleaning for 20 minutes, then rinse with ultrapure water, and finally blow dry with nitrogen;
[0103] (2) Using the preparation method provided in Example 1, a thin film with an optical thickness of one quarter wavelength is prepared on the optical substrate 1 as the high reflectivity film layer 4; using the method of step (3) in Application Example 1, a SiO2 thin film layer with an optical thickness of one quarter wavelength is prepared on the high reflectivity film layer 4 as the low reflectivity film layer 5; repeat the preparation until G|(HL) is completed. 10 L|Air structure, a laser reflection protection optical element with a total of 21 layers of thin films is obtained.
[0104] Characterization and Testing III:
[0105] Figure 8 This is a cross-sectional SEM image of the laser reflection protection optical element containing the thin film obtained in Example 1 in Application Example 2. The film layers are divided by short white lines and the number of film layers is displayed in red numbers. It can be seen from the figure that the film structure consists of 21 layers, and high and low refractive index layers alternate, the darker layers (odd-numbered layers) are cubic rare earth-doped hafnium oxide layers, and the brighter layers (even-numbered layers) are silicon dioxide layers.
[0106] The laser reflection protection optical element made of the thin film obtained in Example 1 in the corresponding use case 2 and the uncoated optical substrate (as application comparison example 2) were tested for transmittance (reflectivity was calculated) and laser damage threshold: the optical transmittance was measured using Shimadzu's SolidSpec-3700i; the laser damage threshold was measured in accordance with the 1-ON-1 method defined in ISO 21254, using a Nd:YAG laser to emit 1064nm, 10ns laser, with a laser repetition rate of 1Hz and a beam spot diameter of 0.8mm.
[0107] Fig. 9 This is a transmittance test chart of the laser reflection protection optical element containing the thin film obtained in Example 1 and the uncoated optical substrate (or uncoated optical element) in Application Example 2. It can be seen from the figure that the reflectivity of the uncoated optical element to the 1064nm wavelength laser is 6.4%, and the reflectivity of the coated optical element to the 1064nm wavelength laser is 99.3%.
[0108] Fig.10 This is a test diagram of the laser damage threshold of the laser reflection protection optical element containing the thin film obtained in Example 1 in Application Example 1. It can be seen from the figure that the laser damage threshold of the coated optical element is 6.68 J / cm 2 .
[0109] It can be seen that by further alternately preparing multiple layers of high-reflective films through the thin film obtained with an appropriate rare earth doping amount, high reflection of lasers at specific wavelengths can be achieved to reduce the damage of lasers to components, thereby obtaining a high-reflective film system with a high laser damage threshold.
[0110] It should be noted that the laser anti-reflection optical element in Application Example 1 and the laser reflection protection optical element in Application Example 2 are both designed for lasers with a wavelength of 1064nm. Therefore, the optical thickness of each of the intermediate layer 2, the protective layer 3, the high reflectivity film layer 4 and the low reflectivity film layer 5 is one quarter of the target laser wavelength 1064n, that is, 266nm. However, it is not limited to lasers with a wavelength of 1064nm. It can be understood that those skilled in the art can reasonably adjust and adjust the optical film thickness based on the properties and optical properties of the obtained cubic phase rare earth doped hafnium oxide film, and / or can reasonably adjust the thickness of the optical film layer in the laser anti-reflection optical element, that is, the laser reflection protection optical element, so that the optical film or optical element can meet the requirements and needs of any selected band or wavelength, so as to achieve the specific optical function of the selected target band laser or wavelength laser. For example, the laser reflection protection optical element can also be applied to lasers with wavelengths of 355nm and 532nm, respectively.
[0111] From the above, it can be seen that the present invention provides a cubic rare earth doped hafnium oxide film and its preparation method and use. The preparation method uses a specific hafnium oxide ceramic target and a rare earth target to perform dual-target magnetron sputtering to obtain a cubic rare earth doped hafnium oxide film. Compared with a single component hafnium oxide film, the rare earth doped hafnium oxide film obtained by the specific preparation method has better high-temperature phase stability, effectively avoids film failure defects caused by high temperature, thereby enhancing its laser damage threshold, which is conducive to the manufacture of more stable laser optical components and provides support for high-energy laser systems.
[0112] The present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
[0113] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0114] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0115] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing a cubic rare earth doped hafnium oxide thin film, characterized in that: The preparation method comprises the steps of using a hafnium oxide ceramic target and a rare earth target for dual-target magnetron sputtering, and allowing the rare earth element to occupy the hafnium lattice site during the deposition process to achieve stable solid solution doping, so as to obtain a cubic phase rare earth-doped hafnium oxide film.
2. The method for preparing a cubic rare earth doped hafnium oxide thin film according to claim 1, characterized in that: The rare earth element in the rare earth target includes at least one of Y, Er, Yb, Eu or Sc; In the cubic rare earth doped hafnium oxide thin film, the molar doping amount of the rare earth element is 5% to 20% of the molar amount of the hafnium oxide.
3. The method for preparing a cubic rare earth doped hafnium oxide thin film according to claim 1 or 2, characterized in that: The rare earth target includes a metal target or a compound target of a rare earth element; the compound target includes an oxide target; The hafnium oxide ceramic target is matched with a radio frequency power supply for magnetron sputtering; when the rare earth target is a metal target, it is matched with a direct current power supply for magnetron sputtering; when the rare earth target is a compound target, it is matched with a radio frequency power supply for magnetron sputtering.
4. The method for preparing a cubic rare earth doped hafnium oxide thin film according to claim 1 or 2, characterized in that: The dual-target magnetron sputtering includes first performing pre-sputtering for 1 to 5 minutes and then performing co-sputtering; In the dual-target magnetron sputtering, the background vacuum of the chamber is 3×10 -5 ~9×10 -4 Pa, argon is used as the working gas, the flow rate of the working gas is 20~60sccm, and the working vacuum is 0.1~1Pa; the sputtering power of the hafnium oxide ceramic target is 200~500W, and the sputtering power of the rare earth target is 10~200W; After the dual-target magnetron sputtering is completed, a composite film is obtained, and the composite film is annealed to obtain the cubic rare earth-doped hafnium oxide film; the annealing temperature is 100-500°C.
5. A cubic rare earth doped hafnium oxide thin film, characterized in that: Obtained according to the preparation method according to any one of claims 1 to 4.
6. Use of the cubic rare earth doped hafnium oxide thin film according to claim 5, characterized in that: The uses include as laser optical films with high laser damage threshold.
7. The use of the cubic rare earth doped hafnium oxide thin film according to claim 6, characterized in that: The use includes a laser anti-reflection optical element; the laser anti-reflection optical element includes an optical substrate and an intermediate layer and a protective layer sequentially arranged thereon, the intermediate layer includes the laser optical film with a high laser damage threshold; the optical thickness of the intermediate layer and the optical thickness of the protective layer are respectively one-quarter of the laser wavelength; The protective layer includes a SiO2 thin film layer.
8. The use of the cubic rare earth doped hafnium oxide thin film according to claim 6, characterized in that: The use includes a laser reflection protection optical element; the laser reflection protection optical element includes G|(HL) 10 L|Air structure, wherein G is an optical substrate, H is a high reflectivity film layer, and L is a low reflectivity film layer, and the high reflectivity film layer includes the laser optical film with a high laser damage threshold; the optical thickness of the high reflectivity film layer and the optical thickness of the low reflectivity film layer are respectively one-fourth of the laser wavelength; The low reflectivity film layer includes a SiO2 thin film layer.
9. Use of the cubic rare earth doped hafnium oxide thin film according to claim 7 or 8, characterized in that: The optical substrate includes at least one of quartz glass, BK7 glass, sapphire glass or organic flexible glass.
10. Use of the cubic rare earth doped hafnium oxide thin film according to claim 7 or 8, characterized in that: The method for preparing the SiO2 thin film layer comprises: using a silicon oxide target with a purity of ≥99.99% to perform magnetron sputtering, controlling the background vacuum of the chamber to 3×10 -5 ~9×10 -4 Pa, argon is used as the working gas, the flow rate of the working gas is 20~60sccm, the working vacuum degree is 0.1~1Pa, the RF power supply is matched, the sputtering power is 100~250W, and pre-sputtering is carried out for 1~5min before formal sputtering.
Citation Information
Patent Citations
Gate dielectric material cubical phase HfO2 film and preparation method thereof
CN101660128A
Method for preparing yttrium-oxide-stabilized hafnium oxide vacuum coating material
CN104446458A
Tantalum-doped hafnium oxide ferroelectric film and preparation method and application thereof
CN116445870A
Optical thin film
JP1998273773A
